Copylefties are in the right. - Wagstaff, Jeremy (Far Eastern Economic Review, 2002)
In the light of the ongoing antitrust case against Microsoft, the writer calls for a statute of limitations on older versions of the software giant's Windows programs. He argues this would allow enthusiasts to develop the underlying code without challenging existing markets.